Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1982
DOI: 10.3382/ps.0610409
|View full text |Cite
|
Sign up to set email alerts
|

Complementation of Major Histocompatibility Haplotypes in Regression of Rous Sarcoma Virus-Induced Tumors in Noninbred Chickens ,

Abstract: Relative responses to Rous sarcoma virus (RSV)-induced tumors were studied in UNH 105 chickens, a noninbred line of New Hampshires. A total of 799 chickens blood typed for B alloantigens were classified into six genotypes: B23/B23, B24/B24, B26/B26, B23/B24, B23/B26, and B24/B26. Chickens were inoculated with subgroup A Rous sarcoma virus in the left wingweb at 6 weeks of age. The in vivo response was evaluated and given a tumor profile index (TPI) based on the change in tumor size over a 10-week period postin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1983
1983
2004
2004

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 16 publications
(11 reference statements)
0
6
0
Order By: Relevance
“…Senseney et al [37] in a cross segregating for two haplotypes (B Q and B 17 ) found no effect of MHC on the regression of tumors at a high dose of virus but an effect at a lower dose of the same virus and in the same genetic stock with an allelic complementation between the two alleles, the heterozygote state showing an advantage towards tumor regression. The superiority of other heterozygote combination were found elsewhere [6,27,39]. The effect of the resistance genes may clearly depend on the degree of pathogenicity of the virus.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Senseney et al [37] in a cross segregating for two haplotypes (B Q and B 17 ) found no effect of MHC on the regression of tumors at a high dose of virus but an effect at a lower dose of the same virus and in the same genetic stock with an allelic complementation between the two alleles, the heterozygote state showing an advantage towards tumor regression. The superiority of other heterozygote combination were found elsewhere [6,27,39]. The effect of the resistance genes may clearly depend on the degree of pathogenicity of the virus.…”
Section: Discussionmentioning
confidence: 92%
“…Three phases may be seen with the lines diverging from each other before becoming closer in terms of genetic values: generations 0-3, 3-8 and 8-18. The second phase (3)(4)(5)(6)(7)(8) corresponds to a period where only one generation of selection could be actually performed (generation 6). As observed for phenotypic values, genetic divergence was maximum at generation 14 (divergence of 1.75 estimated TPI) but diminished at the end of the period analyzed here (divergence of 0.96 estimated TPI).…”
Section: In Progressor and Regressor Selected Linesmentioning
confidence: 99%
“…Contingency table chi-square analysis assessed the incidence of mortality among all genotypes; single degree-of-freedom comparisons were used to evaluate mortality among particular haplotypes. Complementation of the antitumor response among the other haplotypes in the UNH 105 population was found by Collins et al (1979;1985) and Brown et al (1982 (Collins et al, 1979;Brown et al, 1982). 398 >.…”
Section: Methodsmentioning
confidence: 95%
“…Brown et al (1982) conducted an experiment in which all 6 possible genotypes were represented in one generation. Brown et al (1982) conducted an experiment in which all 6 possible genotypes were represented in one generation.…”
Section: The Major Histocompatability Complex (Mhc) or E Complexmentioning
confidence: 99%